W stalinowskim aparacie władzy. Działalność Mieczysława Moczara w okresie IX 1948 – IV 1956 - Lesiakowski, Krzysztof (Acta Universitatis Lodziensis. Folia Historica, 1997)
Mieczysław Moczar was a member of the International Organization for Helping Rewolutionists before 1939. During the World War II he was a district commander of Gwardia Ludowa (People’s Guard) and Armia Ludowa (People’s Army) in Łódź, Lublin and Kielce. He became a chief of the Provincial Office for Public Security (WUBP) of Łódź in January 1945 and then he served in Ministry of Public Security (MBP) for a short time. In the summer of 1948 he was linked with the case of Władysław Gomułka and the so-called rightist-nationalist deviation and finally the communist party reprimended him and debared from central authorities. In September 1948 he started his activity as a voivode and then as a chairman of Województka Rada Narodowa (People’s Provincial Council) in Olsztyn. In April 1952 he took the same post in Białystok and in 1954 in Warsaw, and he was active there to April 1956. The public security service as well as local PZPR (Polish United Workers’ Party) organizations treated him with distrust all this time. He realised all directions of his authorities very actively to save his position in Stalinist elite of power. Such actions as a veryfication of autochthons, showed his attempting to probe his usefulness. The period since September 1948 to April 1956 is poor-known in Moczar’s biography. Although ha was not at the top of power then, his activity generated controversial opinions.